Preliminary Study on Sago Frond Juice as an Inoculum Media for the Growth of Lactococcus lactis 10-1 - Iwana Haziqah, Mohd Taufik (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This research was conducted to study the ability of sago frond juice (SFJ) as an inoculum media for growing Lactococcus lactis 10-1. L. lactis 10-1 is lactic acid producing bacteria which commonly consumes glucose as its carbon source. The bacteria was incubated in four varieties of inoculum media which were SFJ only, SF] with 2.5 gIL yeast extract, SF] with 5 gIL yeast extract whereas commercial glucose (CG) with 5 gIL yeast extract was used as control throughout this study. From the result, SF] with 5 gIL yeast extract and CG with 5 gIL yeast extract exhibited almost similar maximum DCW ofLactocoeeus laetts 10-1. However, in terms of time, the Lactocoecus laetis 10-1 in CG with 5 gIL yeast extract was faster to reach maximum DCW compared to SF] with 5 gIL yeast extract.